Building Peace that Lasts: A Study of State-Led Peacebuilding in Kenya - Githaiga, Nyambura (Université d'Ottawa / University of Ottawa, 2017)
The concept of peacebuilding evokes the image of international interventions in countries emerging from civil wars. Despite the visibility of this engagement, post-civil war peacebuilding is just one form of peacebuilding. As a response to smaller scale violent conflicts, ongoing peacebuilding interrupts cycles of violence and prevents the escalation of violent conflict. The 2007/8 post-election violence in Kenya captured international attention due to the scope and magnitude of the conflict. In 1992 and 1997, Kenya had experienced lower levels of electoral violence. The recurring and escalatory nature of violent conflict implies that peacebuilding should be a strategic response, earlier on, to prevent violence from reaching new levels. Since 2002, the Kenyan state has actively engaged in peacebuilding. This study on state-led peacebuilding in Kenya deviates from the typical post-war interventions to analyse peacebuilding as an ongoing preventative response by national actors to intermittent violence. This thesis seeks to explain the impact of this state-led peacebuilding approach on the practice and prospect of peace. To do so, I first explore the multiple conceptions of peace held by those engaged in this approach to understand what type of peace is being built. Second, I analyse the paradox of the state in peacebuilding and how the role of the state has influenced the nature of peacebuilding and consequently the prospects for peace. The state in peacebuilding presents a paradox because of the state’s direct and indirect involvement in violent conflict as well as the top-down nature of state engagement. Third, I interrogate the relationship between the institutionalisation of peacebuilding and the sustainability of peacebuilding and peace. I find that state-led peacebuilding in Kenya has raised the profile of peacebuilding, improved the synergy between peacebuilding actors and increased the inflow of resources available to build peace. This positive influence is countered by the negative implications of the state’s role in promoting a reductive conceptualisation of peace and unsustainably institutionalising peace building. I conclude that, though the state has a role to play in peacebuilding, the contradictory implications of state-led peacebuilding challenge the sustainability of peacebuilding and peace.
Keywords: peacebuilding; peace; Kenya; violent conflict; infrastructure for peace